2009
DOI: 10.1523/jneurosci.3238-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

NOS2Gene Deficiency Protects from Sepsis-Induced Long-Term Cognitive Deficits

Abstract: To date, long-term consequences of septic encephalopathy on cerebral metabolism, cognition, learning, and memory capabilities and factors involved are poorly understood. In this study, we used a murine sepsis model to demonstrate that bacterial lipopolysaccharide (LPS) causes long-term cognitive deficits in mice. Two months after LPS treatment, wild-type mice committed more working and reference memory errors than controls. The behavioral impairment was independent of the cerebral glucose uptake as evidenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 53 publications
(60 reference statements)
7
105
3
Order By: Relevance
“…Data from animal studies also indicate that hippocampus-dependent learning and memory is permanently attenuated after a septic episode (Barichello et al, 2005(Barichello et al, , 2007Semmler et al, 2007;Weberpals et al, 2009). This is likely to involve apoptosis of neuronal progenitor cells within the dentate gyrus.…”
Section: Cognitive Declinementioning
confidence: 96%
“…Data from animal studies also indicate that hippocampus-dependent learning and memory is permanently attenuated after a septic episode (Barichello et al, 2005(Barichello et al, , 2007Semmler et al, 2007;Weberpals et al, 2009). This is likely to involve apoptosis of neuronal progenitor cells within the dentate gyrus.…”
Section: Cognitive Declinementioning
confidence: 96%
“…25 There is no clear evidence to explain in detail how inflammation reaches the brain during sepsis, but both in animals and in humans, inflammation occurs in the CNS early and late after sepsis. [26][27][28][29] The immune system is a complex, highly adaptive system, 29 and it is integrated with the CNS at several levels to maintain homeostasis. [30][31][32] However, it is possible that activation of the immune system may induce brain dysfunction, and, in fact, sepsis is a major risk factor for occurrence of delirium.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies are being conducted to clarify the impact of the synthesis of nitric oxide by iNOS in infectious diseases and in the development of cognitive decline. Weberpals et al also observed that iNOS gene deficiency prevents cognitive decline in addition to promoting a reduction in gliosis (astrocytes and microglia), proinflammatory cytokines TNF-α and IL-1β release, and reduction of synaptic dysfunction in sepsis model [58].…”
Section: As Shown Inmentioning
confidence: 94%
“…In this way, the induction of iNOS may result in the development of cognitive impairment [71]. Experimental models of sepsis [58] and malaria (unpublished data) have shown that the inhibition of iNOS has a beneficial effect on the central nervous system, particularly by abolishing cognitive decline.…”
Section: Nmda-nnos Pathway and Excitotoxicity Developmentmentioning
confidence: 99%